Implementation of Behavior Modification Techniques in Overcoming Maladaptive Behavior of Children with Special Needs - Rapisa, Dewi Ratih; Kusumastuti, Dewi Ekasari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2022)
Special needs children often behave maladaptively. This has a negative impact on the child and the surrounding environment. The purpose of this study was to describe the results of the implementation of behavior modification techniques in overcoming the maladaptive behavior of special needs children. The literature review method uses the online database search stage through Mendeley, the inclusion and exclusion process for articles in 2019-2021 obtained a total of 146 national scientific articles and after being rechecked, there are 17 literatures that match the criteria, then a descriptive synthesis and analysis is carried out, and the results are presented. The results of the synthesis and analysis show that the application of behavior modification can overcome maladaptive behavior in the social, self-development, and academic aspects of special needs children. Conclusions from 17 articles describe that behavior modification techniques are effective for overcoming maladaptive behavior in autism, ADHD, intellectual disability and hearing impairment.